Mid-Infrared optical absorber based on anisotropic black phosphorus and magnesium fluoride - Abdulkawi, Wazie M.; Aladadi, Yosef T.; Al-Moliki, Yahya Mohammed; Alresheedi, Mohammed Thamer; Mahdi, Mohd Adzir; Abas, Ahmad Fauzi; Ng, Eng Khoon (Springer, 2024)
This paper presents a mid-infrared absorber based on anisotropic black phosphorus (BP) stacked with magnesium fluoride (MgF2). BP has a sufficiently large electronic bandgap, and its high carrier mobility allows for efficient free-carrier absorption in the mid-infrared regimes. Magnesium fluoride is an ideal candidate for the mid-infrared absorber, providing optical transparency, efficient absorption, and antireflection properties due to its low refractive index. Different unit cell shapes were used to examine the absorbance for both the transverse electric mode (TE) and transverse magnetic mode (TM) polarization components. The results show that the absorbance for TM polarization is approximately 48% and 50% at around 7 μm and 12 μm, respectively. For TE polarization, the absorbance occurs at 9 μm with a value of around 8.5%. Rotating the unit cell to be out of phase by 90 degrees from the neighboring unit cell improved the low absorbance to 45%, and the absorbance peak shifted to 17 μm. © The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature 2024.